Computational investigation of two-dimensional borides with planar octacoordinated main group elements. Issue 30 (26th July 2021) - Yang, Jiashu; Yu, Linke; Li, Fengyu
Abstract : AlB4 monolayer is stable in the planar octacoordinate motif and can be used for electrocatalyzing hydrogen evolution reaction. Abstract : In this communication, by means of first principles calculations, we searched stable two-dimensional borides with octacoordinated main group elements, and we found that only AlB4 monolayer is stable in the planar octacoordinate motif through our stability screenings, which can be used for electrocatalyzing the hydrogen evolution reaction.